Pemanfaatan Tanaman Mangrove sebagai Bahan Ecoprint di Kecamatan Mempawah Hilir Kabupaten Mempawah - Siti Puji Lestariningsih; Silvia Uthari Nuzaverra Mayang Mangurai; Munadian Munadian (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Mangrove forest ecosystems that are maintained can be a source of economic income for local communities, including mangrove forests in Mempawah Regency, West Kalimantan. Mangrove plants have considerable potential as natural dyes. One part of the plant is the leaf. The development of natural dyes from leaves is an alternative to produce environmentally friendly products, namely ecoprint. Ecoprint is a natural coloring technique by utilizing plant parts including leaves without using chemicals. Ecoprint knowledge and skills for the surrounding community, especially junior and senior high school students, are important so that creativity is honed and becomes entrepreneurial capital. The purpose of this activity is to evaluate the knowledge, skills, and interests of junior and senior high school students in Mempawah Regency regarding ecoprints from mangrove leaves. Activities are carried out with two methods, namely the lecture method in the form of presentations and the training method. Junior and senior high school students' knowledge was also evaluated by means of questionnaires distributed before and after the activity. All participants can make ecoprints pounding technique using mangrove plants with different color density results. Participants' knowledge about ecoprint, leaf materials, and the advantages of ecoprint increased after the training activities. Ecoprint training activities can be activities that support arts and crafts and science subjects.